Սուֆիական ինքնակատարելագործման ճանապարհի գաղափարն արտահայտող որոշ եզրեր եզդիական կրոնական հիմներում - Ամրյան, Թերեզա («Նաիրի» հրատ.)
Yezidism has preserved many Sufi elements as it is based on the ideology of the Adawia Sufi brotherhood. Some terms expressing the idea of the Sufi Path of Self-Perfection have special significance in Yezidism: they can mainly be encountered in the Yezidi religious hymns and lore. These terms are related to the Sufi Path, its stations and certain phenomena associated with them. Though they have no Sufi interpretation within the contemporary Yezidi world outlook, they have preserved their original Sufi meaning in the texts of the Yezidi religious hymns. Езидизм, будучи сформирован на основе идеологии суфийского ордена Адавия, сохранил многие суфийские элементы. Среди них особое место занимают термины, выражающие идею суфийского пути самосовершенствования, которые упоминаются в езидских религиозных гимнах. Эти термины связаны с суфийским путем, стоянками этого пути и с некоторыми явлениями, ассоциирующимися с этими стоянками. Хотя эти термины не имеют суфийской интерпретации в рамках современного езидского мировоззрения, однако в текстах езидских религиозных гимнов они используются в своем первоначальном суфийском значении.
Keywords: Կրոն; Եզդիականություն